fipB and fipC: two bacterial loci required for morphogenesis of the filamentous bacteriophage f1. - Lopez, J (1985)
We describe the identification of two mutations in bacterial genes, designated as fipB and fipC, which resulted in temperature-sensitive morphogenesis of bacteriophage f1. These mutations mapped at separate loci but had to be present simultaneously to block f1 production at 41.5 degrees C. One mutation defined the locus fipB at 85.3 min on the Escherichia coli linkage map; the other defined the locus fipC, which mapped very close to rpsL at 73 min. Since these mutations did not appear to affect phage DNA replication, gene expression, or protein localization, they probably interfered with the its life cycle at the level of assembly. fipB mutants were partially deficient in adsorption of bacteriophage lambda, and fipB and fipC mutants leaked beta-lactamase into the medium, suggesting that the mutations affect outer-membrane structure or function.